2013
DOI: 10.1007/s00436-013-3589-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo albendazole treatment of Taenia crassiceps cysticerci strain WFU: proliferation, damage, and recovery

Abstract: Taenia crassiceps has been widely experimented as a model for in vitro and in vivo studies on drug responses. The purpose of this study was to treat BALB/c mice infected with T. crassiceps strain WFU with commercially available albendazole and to analyze the reduction in parasite infrapopulations. Here, we describe the reduction and apparent damage of T. crassicceps WFU cysticerci in infected mice after antihelminthic drug treatment and subsequent inoculation of those treated parasites into a naïve host. We we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…With regard to the number of parasites, we used 30 cysticerci in order to ensure their proliferation and correct setting in the peritoneum of the mouse. It has been found that cysts can be damaged during the inoculation procedure (Fragoso et al, 2012;Zurabian et al, 2013). In the present study, the use of 14-gauge needle for inoculation allowed a successful establishment and proliferation of the parasites in all mice.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…With regard to the number of parasites, we used 30 cysticerci in order to ensure their proliferation and correct setting in the peritoneum of the mouse. It has been found that cysts can be damaged during the inoculation procedure (Fragoso et al, 2012;Zurabian et al, 2013). In the present study, the use of 14-gauge needle for inoculation allowed a successful establishment and proliferation of the parasites in all mice.…”
Section: Discussionmentioning
confidence: 79%
“…Also, animal experimentation is an important tool to determine the effectiveness of new drugs in development, including its efficacy and security. Although different strains of T. crassiceps have been used as an alternative model to T. solium for the study of topics such as immunology, genetic, and metabolic pathways (Willms and Zurabian, 2010), only the ORF and WFU strains have been used for the in vivo evaluation of the efficacy of androgens (proposed as anti-parasitic molecules) (Carrero et al, 2010), cysticidal drugs (Zurabian et al, 2013) and new formulations of ABZ (Palomares-Alonso et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful strategies include extensive surgical interventions and protracted anthelminthic drug therapy. Experiments in mice showed a significant reduction of cysticerci after prolonged 20-and 25-day administration of albendazole (Zurabian et al 2013). In human medicine, the synergistic action of praziquantel and albendazole was employed to successfully treat infection (Garcia et al 2011;Fraga et al 2012;Anikpeh et al 2014).…”
Section: Discussionmentioning
confidence: 99%